Seismic survey in an urban area: the activities of the EMERSITO INGV emergency group in Ancona (Italy) following the 2022 Mw 5.5 Costa Marchigiana–Pesarese earthquake - D. Famiani; F. Cara; G. Di Giulio; G. Cultrera; F. Pacor; S. Lovati; G. Riccio; M. Vassallo; G. Brunelli; A. Costanzo; A. Bobbio; M. Pischiutta; et al. (Earth System Science Data)
This paper illustrates the activities of EMERSITO, an emergency task force of the Istituto Nazionale di Geofisica e Vulcanologia (INGV, Italy) devoted to site effects and microzonation studies during the seismic sequence that occurred close to the Adriatic coast in central Italy starting from 9 November 2022, following the Mw 5.5 mainshock localized in the sea. In particular, we describe the steps that led to the deployment of a temporary network of seismic stations in the urban area of Ancona, the main city of the Adriatic coastline. Data collected by the temporary Ancona network (identification code 6N; https://doi.org/10.13127/sd/qctgd6c-3a, EMERSITO Working Group, 2024) from November 2022 to the end of February 2023 have been preliminary analyzed with different techniques to characterize the deployment sites and are now available for further and detailed studies.